Clinical presentation and outcomes of norovirus infection in intestinal allograft compared to native intestine. Issue 3 (27th April 2017) - Florescu, Diana F.; Sonderup, Jessica L.; Grant, Wendy; Chong, Pearlie P.; van Duin, David; Kalil, Andre C.
Abstract: Background: No data are available on clinical manifestations and course of norovirus gastroenteritis (NVE) in intestinal allograft (from intestinal and multivisceral transplant recipients, ITR) compared to native intestine (from other allograft recipients, nITR). Methods: This was a retrospective study of solid organ transplant recipients with NVE at two centers from January 1, 2010 to April 1, 2014. Chi‐square, t‐test, linear and logistic regression analyses were done to compare NVE in ITR vs nITR patients. Results: The ITR (45 patients) were compared to nITR (107 patients). ITR were younger (odds ratio [OR]=0.90; P <.0001), less likely to receive anti‐lymphocyte induction therapy (OR=0.15; P <.0001), and had shorter time from transplant to NVE (OR=0.99; P =.008). On presentation ITR had less frequent nausea (OR=0.11; P <.0001) or vomiting (OR=0.36; P =.01), higher white blood cell count (OR=1.09; P =.001), and higher glomerular filtration rate (OR=1.02; P <.0001). ITR were less likely to receive anti‐motility agents (OR=9.6; P <.0001). ITR were more likely to stay longer on intravenous (IV) fluids (OR=1.18; P <.0001); have recurrent NVE (OR=4.25; P <.0001); have longer hospital stay (OR=1.07; P <.0001); develop acute rejection (OR=5.1; P =.006); and have lower overall survival (OR=0.28; P =.006). Conclusions: Compared to nITR, the ITR with NVE were significantly younger, had less nausea and vomiting at presentation, received less anti‐motility agents, required more IV fluids, and had longer hospital stay. A trend was seen for lower survival with NVE in ITR.